Student research skills development at University - Berezina, Svetlana L.; Safonov, Vladimir A.; Babaskina, Liudmila I. (Opción, 2020)
A review of the global and domestic practice of the application of project-based learning methodologies was carried out from the perspective of the student research skills development; the analysis of the conformity of project-based learning to the standards of Russian higher education has been carried out. As a result, project-based learning is a promising and effective approach to student research skills development. In conclusion, project-based learning is an effective pedagogical approach due to the possibility of being integrated into production and solving real professional problems.